Advances in neurexin studies and the emerging role of neurexin-2 in autism spectrum disorder - Khoja, Sheraz; Haile, Mulatwa T.; Chen, Lulu Y. (Frontiers in Molecular Neuroscience, 2023)
Over the past 3 decades, the prevalence of autism spectrum disorder (ASD) has increased globally from 20 to 28 million cases making ASD the fastest-growing developmental disability in the world. Neurexins are a family of presynaptic cell adhesion molecules that have been increasingly implicated in ASD, as evidenced by genetic mutations in the clinical population. Neurexins function as context-dependent specifiers of synapse properties and critical modulators in maintaining the balance between excitatory and inhibitory transmission (E/I balance). Disrupted E/I balance has long been established as a hallmark of ASD making neurexins excellent starting points for understanding the etiology of ASD. Herein we review neurexin mutations that have been discovered in ASD patients. Further, we discuss distinct synaptic mechanisms underlying the aberrant neurotransmission and behavioral deficits observed in different neurexin mouse models, with focus on recent discoveries from the previously overlooked neurexin-2 gene (Nrxn2 in mice and NRXN2 in humans). Hence, the aim of this review is to provide a summary of new synaptic insights into the molecular underpinnings of ASD.